The art of photography : a personal approach to artistic expression - Barnbaum, Bruce, 1943- (Rocky Nook, 2017)
Featuring nearly 200 beautiful photographs, as well as numerous charts, graphs, and tables, this invaluable book presents how-to techniques to beginner, intermediate, and advanced photographers for both traditional and digital approaches. --